2016
DOI: 10.3906/sag-1511-95
|View full text |Cite
|
Sign up to set email alerts
|

Importance of sonographic paratracheal lymph node evaluationin early autoimmune thyroiditis

Abstract: Careful and thorough review of the PLNs can ensure diagnosis of autoimmune thyroiditis even in cases of early stage of the disease and prevent false-negative diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…In addition to the above symptoms, there are also some changes in local signs, such as goiter (enlarged neck and disappearance of necklines), and enlarged cervical lymph nodes. Some studies found that the prevalence of cervical lymphadenopathy in patients with positive TPOAb or TGAb is approximately 63% ~88.5% (63)(64)(65), and they suggested that cervical lymphadenopathy may be one of the indicators to distinguish thyroiditis from other benign thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above symptoms, there are also some changes in local signs, such as goiter (enlarged neck and disappearance of necklines), and enlarged cervical lymph nodes. Some studies found that the prevalence of cervical lymphadenopathy in patients with positive TPOAb or TGAb is approximately 63% ~88.5% (63)(64)(65), and they suggested that cervical lymphadenopathy may be one of the indicators to distinguish thyroiditis from other benign thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%